Sodium Channel Blockers Modulate Abnormal Activity of Regenerating Nociceptive Corneal Nerves After Surgical Lesion - Luna, Carolina (Invest Ophthalmol Vis Sci, 2021)
PURPOSE: To test the effect of different sodium channel blockers on the electrical activity of corneal nociceptors in intact and surgically injured corneas. METHODS: In anesthetized guinea pigs, a 4-mm diameter corneal flap was performed in one eye at a midstromal depth using a custom-made microkeratome. At different times after surgery (3 hours to 15 days), the electrical activity of corneal nociceptor fibers was recorded from ciliary nerve filaments in the superfused eye in vitro. Mechanical threshold was measured using calibrated von Frey hairs; chemical stimulation was performed applying 30-second CO(2) gas pulses. The characteristics of the spontaneous and stimulus-evoked activity of corneal nociceptors recorded from intact and lesioned corneas, before and after treatment with the sodium channel blockers lidocaine, carbamazepine, and amitriptyline, were compared. RESULTS: No spontaneous or stimulus-evoked impulse activity was detected inside the flap at any of the studied time points. However, both were recorded from mechanonociceptor and polymodal nociceptors fibers in the surrounding corneal tissue, being significantly higher (sensitization) 24 to 48 hours after surgery. In these fibers, none of the tested drugs affected mechanical threshold, but they significantly reduced the CO(2) response of polymodal nociceptors of intact and injured corneas. Likewise, they diminished significantly the transient increase in spontaneous and stimulus-evoked activity of sensitized polymodal nociceptors. CONCLUSIONS: Na(+) channel blockers decrease the excitability of intact and sensitized corneal nociceptor fibers, thus acting as potential tools to attenuate their abnormal activity, which underlies the spontaneous pain, hyperalgesia, and allodynia often accompanying surgical corneal lesions, as occurs after photorefractive surgery.